Cardio‐microcurrent device for chronic heart failure: first‐in‐human clinical study. (9th February 2021) - Kosevic, Dragana; Wiedemann, Dominik; Vukovic, Petar; Ristic, Velibor; Riebandt, Julia; Radak, Una; Brandes, Kersten; Goettel, Peter; Duengen, Hans‐Dirk; Tahirovic, Elvis; Kottmann, Tatjana; Voss, Hans Werner; et al.
Abstract: Aims: Most devices for treating ambulatory Class II and III heart failure are linked to electrical pulses. However, a steady electric potential gradient is also necessary for appropriate myocardial performance and may be disturbed by structural heart diseases. We investigated whether chronic application of electrical microcurrent to the heart is feasible and safe and improves cardiac performance. The results of this study should provide guidance for the design of a two‐arm, randomized, controlled Phase II trial. Methods and results: This single‐arm, non‐randomized pilot study involved 10 patients (9 men; mean age, 62 ± 12 years) at two sites with 6 month follow‐up. All patients had New York Heart Association (NYHA) Class III heart failure and non‐ischaemic dilated cardiomyopathy, with left ventricular ejection fraction (LVEF) <35%. A device was surgically placed to deliver a constant microcurrent to the heart. The following tests were performed at baseline, at hospital discharge, and at six time points during follow‐up: determination of LVEF and left ventricular end‐diastolic/end‐systolic diameter by echocardiography; the 6 min walk test; and assessment of NYHA classification and quality of life (36‐Item Short‐Form Health Survey questionnaire). Microcurrent application was feasible and safe; no device‐related or treatment‐related adverse events occurred. During follow‐up, rapid and significant signal of efficacy ( P < 0.005) was present with improvements in LVEF, left ventricular end‐diastolic diameter, left ventricular end‐systolic diameter, and distance walked. For eight patients, NYHA classification improved from Class III to Class I (for seven, as early as 14 days post‐operatively); for one, to Class II; and for one, to Class II/III. 36‐Item Short‐Form Health Survey questionnaire scores also improved highly significantly. Conclusions: Chronic application of microcurrent to the heart is feasible and safe and leads to a rapid and lasting improvement in heart function and a near normalization of heart size within days. The NYHA classification and quality of life improve just as rapidly.